THE APPLICATION OF VIRTUAL GREENHOUSE EFFECT LABORATORY ON THE MATERIAL OF GLOBAL WARMING SYMPTOMS TO IMPROVE STUDENTS SCIENCE PROCESS SKILLS - HASAN, IBRAHIM; , MADLAZIM (Inovasi Pendidikan Fisika, 2018)
Guided inquiry learning model with laboratory activities is one of the learning model that facilitates students to do the discovery in guidance. The results of interviews in 1 Manyar Senior High School showed that 50% students got low score under the minimum mastery criteria especially on the subject of global warming symptoms in which one of the factors is caused by the lack of activity in the form of invention. Based on that, the researcher applied guided inquiry learning model by using virtual laboratory to improve the students? process skill. The purpose of this study is to describe the implementation of learning model by using virtual laboratoirum to improve students science process skills and to describe the students? responses on the material of global warming symptoms. This research used quantitative research type with pre-experimental research design by using one group pretesst-posttest design with one experiment class and two replication classes. The data collection methods used were observation, test, and questionnaire. The data that was obtained in the form of pretest and posttest result were analyzed by using normality test, homogeneity test, t-test and normalized gain test. The results of the research are: a) the learning implementation in the three classes observed from the teachers activities was well executed; b) based on gain analysis, students science process skills on the material of global warming symptoms after using the virtual laboratories increased significantly; c) the learning got positive responses from the students with very good category. Based on that, it can be concluded that the application of virtual laboratory can improve the students science process skill. Keywords: Virtual laboratory, students science process skills, global warming symptoms and guided inquiry learning model